Public Response and the Role of New Media in Dissemination of MUI Edict No. 4/2014 on Illegal Wildlife Trade - Dewinta Febriyanti; Fachruddin Majeri Mangunjaya; Tatang Mitra Setia; Yeremiah R. Tjamin; Gugah Praharawati (Journal of Tropical Biodiversity, 2022)
The sophisticated communications could be a tool as a driver to increase of the illegal wildlife trade. Since 2012 there has been a shift in the trend of illegal wildlife trade from the offline market to the online market (advertising, e-commerce and social media). This study aims to determine the role of new media in the dissemination of Indonesian Council of Ulama (MUI) Fatwa No. 4/2014 about The Protection of Endangered Species for the Balance of the Ecosystem (illegal wildlife trade fatwa). The research was carried out in April–August 2020 through the new media Facebook. Collecting wildlife trade data through Google trends for a period of 5 years (2015-2020). Google trends are used as a basic reference in determining targets for video dissemination through Facebook. The approach used is by using research methods through new media, content analysis resulting from video dissemination (such as impressions, engagement, opinions, and feelings). The results of the study show that new media can be an effective medium in conveying and developing conservation messages, particularly to reduce the illegal wildlife trade in Indonesia.